E-learning as an integral part of the educational environment - Solovyova, Olga; Gayduk, Lidiya; Соловйова, Ольга Володимирівна; Гайдук, Лідія Прокопівна (My University, 2021)
With the development of the information sphere, life of a modern person is strongly connected with modern information systems and technologies. Information penetrates into a person's life, regardless his gender, activity, age, gender, etc. and becomes an integral part of it. In modern realities for successful and effective professional activities, the teacher is obliged to use all the opportunities of information technologies.